THE BINARY CHARACTER OF THE CATEGORY "WONDER" - Uldona Abdurahmonova (Journals Park Publishing, 2023)
In this article, the essence and binary nature of the category of "surprise" are studied on the example of Alisher Navoi's works "Lison ut-tayr" and "Hayrat ul-abror".
Keywords: wonder, binary, enlightenment, self, faith, heart, soul, knowledge, imagination, thinking.